1999
DOI: 10.1523/jneurosci.19-02-00578.1999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zolpidem on Miniature IPSCs and Occupancy of Postsynaptic GABAAReceptors in Central Synapses

Abstract: GABAA-mediated miniature IPSCs (mIPSCs) were recorded from layer V pyramidal neurons of the visual cortex using whole-cell patch-clamp recording in rat brain slices. At room temperature, the benzodiazepine site agonist zolpidem enhanced both the amplitude (to 138 +/- 26% of control value at 10 microM) and the duration (163 +/- 14%) of mIPSCs. The enhancement of mIPSC amplitude was not caused by an increase of the single-channel conductance of the postsynaptic receptors, as determined by peak-scaled non-station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
159
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(192 citation statements)
references
References 41 publications
29
159
4
Order By: Relevance
“…It would be interesting to know whether the enhanced GABAergic function contributed to the periodic reduction of seizure severity. The weighted decay time constant of mIPSCs in the present study was larger than previously reported values at room temperature (McIntyre et al 2002;Perrais and Ropert 1999). However, our recordings were performed at a temperature range (19 -23°C) lower than that of the above-cited studies (22-26°C).…”
Section: Plastic Changes Of Gaba a -Receptor Function During Developmcontrasting
confidence: 79%
See 1 more Smart Citation
“…It would be interesting to know whether the enhanced GABAergic function contributed to the periodic reduction of seizure severity. The weighted decay time constant of mIPSCs in the present study was larger than previously reported values at room temperature (McIntyre et al 2002;Perrais and Ropert 1999). However, our recordings were performed at a temperature range (19 -23°C) lower than that of the above-cited studies (22-26°C).…”
Section: Plastic Changes Of Gaba a -Receptor Function During Developmcontrasting
confidence: 79%
“…Diazepam modulation of mIPSC amplitude may be age dependent; potentiation of GABA-evoked currents (Zhang et al 2004) and mIPSC amplitudes (Cohen et al 2000;Defazio and Hablitz 1998;Hajos et al 2000;Nusser et al 1997;Perrais and Ropert 1999) has been observed in juvenile neurons including hippocampal dentate granule cells. In addition, the potentiating effect of diazepam may also be temperature dependent (Perrais and Ropert 1999).…”
Section: Seizure-induced Alterations Of Gaba a -Receptor Allosteric Mmentioning
confidence: 99%
“…The GABA concentration dependence correlated with the relative affinities of ␥2 and ␦ subunit-containing GABARs for GABA: EC 50 values for ␣6/␦ subunit-containing GABARs are ϳ500 -700 nM, whereas for ␣6/␥2 subunit-containing GABARs, they are 2-20 M (Hanchar et al, 2005). This correlation between GABA affinity and benzodiazepine modulation is consistent with proposed mechanisms of benzodiazepine action in which the modulators increase the effective affinity of GABA (Perrais and Ropert, 1999). At higher steady-state GABA concentrations, benzodiazepines become less effective because the binding sites are fully occupied by GABA.…”
supporting
confidence: 81%
“…4C). However, the concentration of synaptically released GABA in the inhibitory cleft is thought to be only 300 -500 M (Jones and Westbrook, 1995;Perrais and Ropert, 1999), and the concentration that spills over to nearby glutamatergic synapses, and so is available for endocytosis, would be even lower (Rusakov et al, 1999).…”
Section: Discussionmentioning
confidence: 99%